Risk Factors Associated with Perineal Lacerations During Vaginal Delivery at Aura Syifa Hospital, Kediri in 2025 - Maringga, Estin Gita; Mustofa, Linda Andri; Lestari, Heni Puji (Jurnal Kebidanan Midwiferia, 2026)
Perineal laceration remains one of the most frequently encountered complications in vaginal childbirth, potentially resulting in significant maternal discomfort and, in severe conditions, contributing to adverse maternal outcomes. Based on data that observed at RS Aura Syifa, where 81.1% of spontaneous deliveries in 2024 involved perineal laceration. This study was aimed to explore determinants associated with the occurrence of perineal lacerations among vagonal birth  at RS Aura Syifa in 2025. A retrospective approach was applied utilizing secondary data derived from hospital medical records. The study encompassed deliveries recorded between January and December 2025. The target population included all women with term gestation who underwent vaginal birth with cephalic fetal presentation, about 725 cases. A total of 209 subjects were selected through a simple random sampling method. Data management procedures involved verification, coding, and tabulation prior to statistical analysis using stata software. Analytical methods included descriptive (univariate), associative (bivariate), and predictive (multivariate) analyses using logistic regression. The results showed that parity as a statistically significant predictor of perineal laceration (p = 0.035). The calculated odds ratio (Exp(B) = 0.117) indicates that women with prior childbirth experience (multiparous and grand multiparous) exhibited a markedly reduced likelihood of sustaining perineal trauma compared to first-time mothers (primiparous). These findings highlight the importance of comprehensive delivery planning and appropriate intrapartum management to reduce the risk of maternal pain and minimize injury to the perineal laceration during vaginal birth.